1997
DOI: 10.3109/17453679709003974
|View full text |Cite
|
Sign up to set email alerts
|

Heterotopic ossification after total knee arthroplasty: 54/615 cases after 1-6 years' follow-up

Abstract: (1997) Heterotopic ossification after total knee arthroplasty: 54/615 cases after 1-6 years' follow-up, Acta Orthopaedica Scandinavica, 68:1, 46-50,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
41
0
6

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 10 publications
0
41
0
6
Order By: Relevance
“…In addition, if rhGDF-5 had been effective outside the osteochondral defect for ectopic bone formation, we would have expected much better bone regeneration in the osteochondral defects themselves, which were filled directly with the growth factor carrier. Many articles were published, describing heterotopic ossification either after knee arthroplasty (Rader et al 1997;Barrack et al 2002;Iorio and Healy 2002;Toyoda et al 2003;Dalury and Jiranek 2004), knee ligament reconstruction (Patton and Tew 2000) or after retrograde nailing of femur fractures (Gosselin et al 1993;Horne and Blue 1999). One reason for the occurrence of heterotopic ossifications after opening the bone marrow from inside a joint is thought to be the "seeding" of bone marrow stem cells, which may lead to ectopic bone formation within the joint capsule, the surrounding muscles or the patellar tendon.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, if rhGDF-5 had been effective outside the osteochondral defect for ectopic bone formation, we would have expected much better bone regeneration in the osteochondral defects themselves, which were filled directly with the growth factor carrier. Many articles were published, describing heterotopic ossification either after knee arthroplasty (Rader et al 1997;Barrack et al 2002;Iorio and Healy 2002;Toyoda et al 2003;Dalury and Jiranek 2004), knee ligament reconstruction (Patton and Tew 2000) or after retrograde nailing of femur fractures (Gosselin et al 1993;Horne and Blue 1999). One reason for the occurrence of heterotopic ossifications after opening the bone marrow from inside a joint is thought to be the "seeding" of bone marrow stem cells, which may lead to ectopic bone formation within the joint capsule, the surrounding muscles or the patellar tendon.…”
Section: Discussionmentioning
confidence: 98%
“…However, this was disputed in other studies that demonstrated no significant correlation between approach, sex, and type of femoral component fixation on the prevalence of HO [21][22][23]. After total knee arthroplasty, women with hypertrophic arthrosis are considered at greater risk of HO [24,25]. Additionally, increased lumbar bone mineral density was shown to be correlated with HO [26].…”
Section: Introductionmentioning
confidence: 89%
“…18 However, in our patient, HO has progressed for 9 years from 1996 to 2004. Surgical excision is recommended for large symptomatic HO, 19 but manipulation under anaesthesia followed by indomethacin for 2 months and aggressive physiotherapy is also recommended. 20,21 Combination of surgery and radiotherapy is also suggested.…”
Section: Discussionmentioning
confidence: 99%